The Implementation of Cake English Learning Appplication in Teaching Pronunciation for EFL Secondary School Graders - Ummi Qalsum Arif; Emilia Triaryeti Kleden (English Learning Innovation, 2025)
This study explores the implementation of the Cake English Learning App as a tool to enhance pronunciation skills among eighth-grade students at SMPN 1 Larantuka. Employing a qualitative approach, data were gathered through classroom observations and interviews with students and teachers to assess the app’s effectiveness and identify its strengths and weaknesses. The results show that the app’s interactive features, such as gamified quizzes, video lessons, and speech recognition, significantly improved student engagement, motivation, and pronunciation accuracy. Students particularly appreciated activities like quizzes and short educational films, which provided an immersive and enjoyable learning experience. However, several challenges emerged, including the app’s reliance on a stable internet connection, the need for adequate device storage, and access to premium features requiring additional payments. Furthermore, some students noted limitations, such as a lack of translations in certain video tutorials and interruptions caused by advertisements. Despite these drawbacks, students expressed positive reactions, citing the app’s user-friendly interface and the ability to practice independently at their own pace as key benefits. To address these issues, solutions such as expanding offline access, offering more instructional videos, and reducing dependency on ads were proposed. This study underscores the potential of mobile-assisted language learning tools, particularly in rural or resource-limited settings, as an effective supplement to traditional teaching methods. By integrating technology like the Cake App, educators can enhance pronunciation instruction, foster student confidence, and create a more engaging classroom environment. The findings contribute to the growing discourse on leveraging digital tools in language education, offering practical recommendations for their integration into curricula to support learners’ linguistic development and address contextual challenges.